The whole town's talking [large type] : a novel - Flagg, Fannie (Random House Large Print, 2016)
"Elmwood Springs, Missouri, is a small town like any other, but something strange is happening out at the cemetery. 'Still Meadows, ' as it's called, is anything but still. Tells a surprising story of life, afterlife, and the mysterious goings-on of ordinary people"--Amazon.com.